2006
DOI: 10.1159/000098221
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sensitization to Peanut Is Highly Enhanced by Application of Peanut Extracts to Intact Skin, but Is Prevented when CpG and Cholera Toxin Are Added

Abstract: Background: CpG oligonucleotides might offer an alternative to conventional immunotherapy in preventing and potentially reversing Th2-biased immune deregulation which leads to allergy. However, non-invasive ways of administration, especially in peanut-allergic patients, should be explored. Methods: One hundred micrograms of whole peanut protein extract (PE) alone, or mixed with cholera toxin (CT, 50 µg) plus CpG (100 µg) as adjuvant, was applied on intact skin of mice (40 min, twice). Initiation of an immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…Conversely, low levels of TNFa and no IFNg or IL-12 were detected which demonstrates that intra-gastric administrations of PE plus CT induced both Th2 and Th17 cells. As previously reported (Adel-Patient et al, 2007), Ara h 1 is the most potent Th2 (and Th17) inducer of cytokines production (data not shown). Conversely, we did not observe cytokine productions after reactivation of splenocytes from mice administered PBS, PE alone or PE plus Cry1Ab (Figure 2).…”
Section: Cytokine Productions By Splenocytes After Antigen Reactivationsupporting
confidence: 88%
“…Conversely, low levels of TNFa and no IFNg or IL-12 were detected which demonstrates that intra-gastric administrations of PE plus CT induced both Th2 and Th17 cells. As previously reported (Adel-Patient et al, 2007), Ara h 1 is the most potent Th2 (and Th17) inducer of cytokines production (data not shown). Conversely, we did not observe cytokine productions after reactivation of splenocytes from mice administered PBS, PE alone or PE plus Cry1Ab (Figure 2).…”
Section: Cytokine Productions By Splenocytes After Antigen Reactivationsupporting
confidence: 88%
“…Most experimental models of food allergy sensitization use an adjuvant, mainly CT, for the intra-gastric route. A previous study demonstrated that epidermal exposure can further enhance sensitisation induced via the oral route using CT [46]. Here, we demonstrate that when the pre-exposure is efficient, i.e.…”
Section: Discussionsupporting
confidence: 59%
“…There is some epidemiological evidence to suggest that this alternative route may be through the skin, as it has been reported that exposure to peanut-containing creams was more common in children who became allergic to peanuts (86% of peanut allergics) than in control infants, either atopic but not peanut allergic (53%) or non-atopic (52%) (Lack et al, 2003). Furthermore, there is evidence from several laboratories using experimental (animal) models that the skin may represent a very effective route for the development of type 2 (IgE-mediated) immune responses (Adel-Patient et al, 2007;Strid et al, 2006).…”
Section: Introductionmentioning
confidence: 99%